The effects of plan decisions on traditional center pattern-The case of Bergama - Gorucu, Elif Ozel; Berkmen, Naime Hulya (KARE PUBL, 2022)
Traditional centers have unique patterns where trade, administration, finance, education, culture, entertainment and meeting places are located, naturally formed according to the geography, history, culture and life styles of a period and/or periods with monumental structures, examples of civil architecture, experiences and cultural features. The factors that ensure authenticity in traditional centers are the relations between the users and the commercial-religious structures, the positions, the orientations and the axes formed between these structures. The traditional center of Bergama, which was named in the World Heritage List with its historical and cultural identity,was formed in line with the commercial and religious elements that were built in the Ottoman period and developed in the historical process. However, Bergama traditional center was deprived of the conservation plan for a long time and was included in the non-conservation plan and it was exposed to physical deterioration. In this study, the characteristics of traditional central pattern, the formationdevelopment-change processes of the pattern, decisions that cause the deterioration, the 2012 approval dated 1/1000 scale Bergama Urban+III. Archaeological Site Conservation Plan decisions and plan notes were presented in line with the determinations in the traditional center in 2009 and 2018 and the researches carried out in the archives of the Directorate of Izmir 2(nd) Regional Cultural Heritage Conservation Board. As a result of the researches and determinations made, the effectiveness of the practices for the conservation and sustainability of traditional centers were discussed and suggestions were presented.
Keywords: Bergama; traditional center; traditional center pattern; Public Administration